A distributed multiple-heat source staged heating method in an electric vehicle. (May 2020) - Ding, Peng; Wang, Zhong; Wang, Ying; Li, Kaiyun
Abstract: A distributed multi-heat source phased control method was designed with the aim of reducing the heating energy consumption of electric vehicles. The method uses multiple-heat sources, namely battery cooling waste heat, motor cooling waste heat and heat pump air conditioning, to heat vehicles in stages. To design this method, the heat generated by an electric vehicle heating system was first numerically analysed. The distribution regions of various heat sources were then optimised and the functional relationships between the heat produced by multiple heat sources were established. The law of temperature distribution in different regions of automobiles was explored for heat produced by multiple heat sources. The method can synthesise the temperature difference outside of the car, the heat release sequence of the heating components and the comfort requirements of passengers. It can also reasonably select the working mode of warm air. A low-temperature test of warm air conditioning was carried out to compare the difference between this method and the conventional heating method of new energy vehicles. The system saved 60% energy while running at an ambient temperature of −22 °C for 2 h. No power battery energy was needed at −5 °C, verifying the superiority of the proposed method. Highlights: A method of multi-heat source sectional cooperative control for heating and air conditioning of new energy vehicles was studied. New energy vehicles were heated with motor waste heat and battery waste heat. The functional relationships between the heating capacities of multi-heat sources were established. The law of temperature distribution in each area of an automobile during heating was explored. Specific test conditions demonstrated energy savings of 100% and 60%.